FAKTOR-FAKTOR SANTRI MUSTHAFAWIYAH LEBIH MEMILIH BANK KONVENSIONAL DARIPADA BANK SYARIAH - Siti Kholijah (EKSYA : Jurnal Ekonomi Syariah, 2023)
Banking according to Law No. 10 of 1998 concerning amendments to Law No. 7 of 1992 concerning banking, is a business entity that collects funds from the public in the form of deposits and distributes them to the public in the form of credit and or other forms in order to improve the lives of many people. since 1992 Indonesia has adopted two banking systems, namely conventional and sharia banking systems. In Islam it is clearly stated that Allah SWT has forbidden usury. On this basis, it is not allowed to transact using Conventional Banks because it clearly contains usury. Some scholars have also forbidden to make transactions using Conventional Banks because it is clearly seen to contain usury. This research uses the type of field research (Field Research) which is carried out directly by researchers by going into the field to interview students and teachers who are in the Musthafawiyah Purba Baru Islamic boarding school. The problem discussed is the factor that students prefer to use Conventional Banks rather than Islamic Banks. Some of the factors that influence students to make transactions using Conventional Banks are: location, service, family, self-concept, and reference group factors. From the above factors, there are several factors that can be seen to cause an exhaustion for families to send their children's school fees. Thus it can be said that if an action can cause fatigue for someone then it is permissible to take other actions that do not cause fatigue. But it would be better if parents and students use Sharia Banks to conduct transactions to avoid usury.